Kinerja BUMN di Indonesia: Kompensasi Eksekutif, Leverage, Size, dan Kepemilikan Manajerial - Hesty Erviani Zulaecha (Universitas Muhammadiyah Prof. DR HAMKA., 2017)
The purpose of this study to determine the influence of executive compensation, leverage, company size and managerial ownership on the performance of state-owned companies in Indonesia. Executive compensation is seen from the amount of compensation granted to directors, leverage is measured by the ratio of DER, the size of the firm views of total assets, managerial ownership seen from the percentage of managerial ownership. The company's performance using ratios Return On Equity. This study used a sample of state-owned enterprises listed on the Stock Exchange during the years 2012-2015 by using purposive sampling method. The data used were obtained from the annual financial statements listed in the Indonesia Stock Exchange. There are 19 companies that meet the criteria. The analytical method used in this study is a multivariate regression. The results showed that the executive compensation and leverage have significant influence while the size of the company and managerial ownership has a weak influence on the performance of state-owned companies in Indonesia.